PROSES PELAKSANAAN DESENTRALISASI ADMINISTRASI PADA PEMERINTAH PROVINSI JAMBI - Zarmaili Zarmaili (Jurnal Ilmiah Universitas Batanghari Jambi, 2012)
One of the objectives of  the implementation of the decentralization concept in a government is to create a clean government, proportional and community service can be carried out efficiently, effectively and responsibly. This study reveals how the shape of the implementation of the decentralization concept in Jambi Provincial Government. With diskritif qualitative methods, data obtained from interviews some Jambi Provincial Government officials, legislators and community of Jambi selected at random, observational approach was also made to the process of implementation activities of Government bureaucracy of Jambi Provincial. The results obtained are  the implementation of the concept of decentralization in Jambi Provincial Government has not done well, bureaucratic form has not been done efficiently, effectively and responsibly. This is evidenced by the failure of obtaining an unqualified (WTP) in 2012 and several officials and former officials are corruption.Keywords: transparent, efficient, effective and accountable.